Existence of solutions for semi-linear abstract differential equations with not instantaneous impulses - Pierri, Michelle; O’Regan, Donal; Rolnik, Vanessa (Applied mathematics and computation, 2013)
In this paper, using the theory of analytic semigroup and fractional power of closed operators we study the existence of solutions for a class of semi-linear abstract impulsive differential equations with not instantaneous impulses. Some applications involving partial differential equations with impulses are presented.